A Cluster of Bacillus cereus Bacteremia Cases among Injection Drug Users - Michael A Benusic; Natasha M Press; Linda MN Hoang; Marc G Romney (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bacillus cereus is a ubiquitous spore-forming organism that is infrequently implicated in extraintestinal infections. The authors report three cases of B cereus bacteremia among injection drug users presenting within one month to an urban tertiary care hospital. Treatment with intravenous vancomycin was successful in all three cases. While temporal association suggested an outbreak, molecular studies of patient isolates using pulsed-field gel electrophoresis did not suggest a common source. A review of the association of B cereus infections with heroin use and treatment of this pathogen is provided.